O controle dos negócios jurídicos processuais da fazenda pública: da liberdade de negociação à preservação do interesse público. - Melo, Rodrigo Tenório Tavares de (2018)
How occurs the control of procedural contracts closed by Public Administration, whereas must be observed the limits about public interest? To answer that question, firstly, it is discussed the ideas about public interest and satellit questions, such as the possibility of public interest's negotiation. After, it is developed a debate about procedural contracts in public administration, its limits and possibilities, besides the kind of control must exists in these contracts. ln regard to methodology, it is adopted bibliographical research and review, to aim a development of the theories about the theme. Afterwards, with use of case study research techniques, its analised a procedural contract accomplished by Public Administration, make a comparison between it and the theory initially developed. Finally, it is verified that the procedural contracts closed by Public Administration needs some kind of increase of the rules that already exists, in view of the difference between public and private negotiations, considering the plenty of restrictions that the public area is conditioned. On account of that, it is showed recomendations for a better control.